Stationary Nickel-Zinc Secondary Battery
The nickel zinc secondary battery design with an LDH separator and sideways placement addresses zinc dendrite-induced short circuits, enhancing cycle life and performance by evenly distributing electrolyte concentration.
Patent Information
- Application Number
- JP2021058863
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-03-30
- Publication Date
- 2025-02-04
- Estimated Expiration
- 2041-03-30
AI Technical Summary
Zinc dendrites in nickel zinc secondary batteries cause short circuits, reducing the charging and discharging life of the battery.
A nickel zinc secondary battery design with a layered double-hydroxide (LDH) separator is used to prevent zinc dendrite penetration, combined with a hydroxide iontophorator to isolate the positive and negative electrodes, and a sideways placement of the battery to evenly distribute electrolyte concentration.
The sideways battery placement and LDH separator effectively prevent zinc dendrite short circuits, significantly improving the cycle life and performance of the battery.
Smart Images

Figure 0007626646000002 
Figure 0007626646000003 
Figure 0007626646000004
Abstract
Description
[Technical field]
[0001] The present invention relates to a stationary nickel-zinc secondary battery. [Background technology]
[0002] In zinc secondary batteries such as nickel-zinc secondary batteries and air-zinc secondary batteries, it is known that metallic zinc precipitates in the form of dendrites from the negative electrode during charging, penetrates the voids in the separator such as nonwoven fabric, and reaches the positive electrode, resulting in a short circuit. Such a short circuit caused by zinc dendrites shortens the repeated charge-discharge life.
[0003] In order to address the above problems, a battery has been proposed that includes a layered double hydroxide (LDH) separator that selectively allows hydroxide ions to pass through while preventing the penetration of zinc dendrites. For example, Patent Document 1 (WO 2013 / 118561) discloses that an LDH separator is provided between the positive and negative electrodes in a nickel-zinc secondary battery. In addition, Patent Document 2 (WO 2016 / 076047) discloses a separator structure that includes an LDH separator fitted or joined to a resin outer frame, and that the LDH separator has such high density that it is gas impermeable and / or water impermeable. This document also discloses that the LDH separator can be composited with a porous substrate. Furthermore, Patent Document 3 (WO 2016 / 067884) discloses various methods for obtaining a composite material by forming an LDH dense membrane on the surface of a porous substrate. This method includes a step of uniformly attaching an initiator substance capable of providing an initiator for the crystal growth of LDH to a porous substrate, and subjecting the porous substrate to hydrothermal treatment in a raw aqueous solution to form a dense LDH membrane on the surface of the porous substrate. An LDH separator has also been proposed that achieves further densification by roll pressing a composite material of LDH / porous substrate produced through hydrothermal treatment. For example, Patent Document 4 (International Publication No. 2019 / 124270) discloses an LDH separator that includes a polymeric porous substrate and an LDH filled in the porous substrate, and has a linear transmittance of 1% or more at a wavelength of 1000 nm.
[0004] In addition, although they cannot be called LDH, LDH-like compounds are known as hydroxides and / or oxides with a layered crystal structure similar to LDH, and exhibit hydroxide ion conductive properties similar to LDH and can be collectively called hydroxide ion conductive layered compounds together with LDH. For example, Patent Document 5 (International Publication No. 2020 / 255856) discloses a hydroxide ion conductive separator comprising a porous substrate and a layered double hydroxide (LDH)-like compound that blocks the pores of the porous substrate, the LDH-like compound being a layered crystal structure hydroxide and / or oxide containing Mg and one or more elements including at least Ti selected from the group consisting of Ti, Y, and Al. This hydroxide ion conductive separator is said to have superior alkali resistance and to be able to more effectively suppress short circuits caused by zinc dendrites compared to conventional LDH separators.
[0005] Incidentally, Patent Document 6 (WO 2019 / 069760) and Patent Document 7 (WO 2019 / 077953) propose a zinc secondary battery in which the entire negative electrode active material layer is covered or wrapped with a liquid-retaining member and an LDH separator, and the positive electrode active material layer is covered or wrapped with a liquid-retaining member. A nonwoven fabric is used as the liquid-retaining member. With this configuration, it is said that a zinc secondary battery (especially a stacked battery thereof) capable of preventing zinc dendrite extension can be produced extremely easily and with high productivity, eliminating the need for complicated sealing and joining between the LDH separator and the battery container. [Prior art documents] [Patent documents]
[0006] [Patent Document 1] International Publication No. 2013 / 118561 [Patent Document 2] International Publication No. 2016 / 076047 [Patent Document 3] International Publication No. 2016 / 067884 [Patent Document 4] International Publication No. 2019 / 124270 [Patent Document 5] International Publication No. 2020 / 255856 [Patent Document 6] International Publication No. 2019 / 069760 [Patent Document 7] International Publication No. 2019 / 077953 Summary of the Invention
[0007] Incidentally, when the above-mentioned conventional nickel-zinc secondary battery is used as a stationary battery, the battery is currently arranged vertically with the electrode plates vertical.
[0008] The present inventors have now discovered that the cycle life of a nickel-zinc secondary battery can be significantly improved by orienting the battery horizontally with the electrode plates lying horizontally.
[0009] It is therefore an object of the present invention to significantly improve the cycle life of stationary nickel-zinc secondary batteries.
[0010] According to one aspect of the present invention, a positive electrode plate including a positive electrode active material layer including nickel hydroxide and / or nickel oxyhydroxide; a negative electrode plate including a negative electrode active material layer including at least one selected from the group consisting of zinc, zinc oxide, a zinc alloy, and a zinc compound; a hydroxide ion conductive separator that separates the positive electrode plate and the negative electrode plate so as to be capable of conducting hydroxide ions; an electrolyte in which the positive electrode plate, the negative electrode plate, and the hydroxide ion conductive separator are immersed; wherein the positive electrode plate, the hydroxide ion conducting separator and the negative electrode plate are stacked vertically in a horizontal orientation, thereby disposing the unit cell in a horizontal orientation. [Brief description of the drawings]
[0011] [Figure 1]FIG. 2 is a schematic cross-sectional view conceptually showing a stationary nickel-zinc secondary battery of the present invention arranged horizontally, which corresponds to the battery arrangement in Example 1. [Diagram 2] FIG. 2 is an exploded perspective view showing an example of the internal structure of the stationary nickel-zinc secondary battery shown in FIG. [Diagram 3] FIG. 2 is a conceptual diagram showing, in shading, the distribution of electrolyte concentration estimated in a stationary nickel-zinc secondary battery of the present invention that is arranged horizontally. [Figure 4] FIG. 2 is a cross-sectional view showing a schematic diagram of another example of a battery element of the stationary nickel-zinc secondary battery of the present invention. [Diagram 5] FIG. 2 is a perspective view of a stationary nickel-zinc secondary battery prepared and arranged in Example 1. [Figure 6] FIG. 1 is a schematic cross-sectional view conceptually showing a stationary nickel-zinc secondary battery arranged at an angle of 45 degrees to the horizontal plane, which corresponds to the battery arrangement in Example 2 (Comparative Example). [Figure 7] FIG. 2 is a perspective view of a stationary nickel-zinc secondary battery prepared and arranged in Example 2 (Comparative Example). [Figure 8] FIG. 1 is a schematic cross-sectional view conceptually showing a conventional stationary nickel-zinc secondary battery arranged vertically, which corresponds to the battery arrangement in Example 3 (Comparative Example). [Figure 9] FIG. 1 is a conceptual diagram showing, in shading, the estimated electrolyte concentration distribution in a conventional stationary nickel-zinc secondary battery arranged vertically. [Figure 10] FIG. 2 is a perspective view of a stationary nickel-zinc secondary battery prepared and arranged in Example 3 (Comparative Example). DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0012] Stationary Nickel-Zinc Secondary Battery FIG. 1 conceptually illustrates a stationary nickel-zinc secondary battery according to the present invention, while FIG. 2 illustrates an example of the internal structure of a nickel-zinc secondary battery. A stationary nickel-zinc secondary battery is a stationary nickel-zinc secondary battery that is installed after a predetermined space is secured, and is distinguished from a portable nickel-zinc secondary battery. A stationary nickel-zinc secondary battery 10 illustrated in FIGS. 1 and 2 includes a battery element 11 in a battery case 20, and the battery element 11 includes a unit cell including a positive electrode plate 12, a negative electrode plate 14, a hydroxide ion conductive separator 16, and an electrolyte (not shown). The positive electrode plate 12 includes a positive electrode active material layer including nickel hydroxide and / or nickel oxyhydroxide. The negative electrode plate 14 includes a negative electrode active material layer including at least one selected from the group consisting of zinc, zinc oxide, zinc alloy, and zinc compound. The hydroxide ion conductive separator 16 separates the positive electrode plate 12 and the negative electrode plate 14 in a manner that allows hydroxide ion conductivity. The positive electrode plate 12, the negative electrode plate 14, and the hydroxide ion conductive separator 16 are immersed in an electrolyte. The positive electrode plate 12, the hydroxide ion conductive separator 16, and the negative electrode plate 14 are stacked vertically in a horizontal orientation, thereby forming a horizontal arrangement of a unit cell. By thus orienting the nickel-zinc secondary battery 10 horizontally with the electrode plates horizontal, the cycle life is significantly improved.
[0013] That is, as described above, when a conventional nickel-zinc secondary battery is used as a stationary battery, the battery is currently arranged vertically so that the electrode plates are vertical. This is because there was a fixed idea that a vertical arrangement would be advantageous in terms of battery manufacturing and performance. However, unexpectedly, it was found that the cycle life is significantly improved simply by arranging the nickel-zinc secondary battery 10 horizontally so that the electrode plates are horizontal. This is thought to be because, as conceptually shown in FIG. 3 by the concentration of the electrolyte 18 being light and dark, when the battery is placed horizontally, the electrolyte 18 spreads more evenly over the negative electrode plate 14, reducing reaction unevenness, thereby improving cycle performance. That is, in the case of the conventional vertical arrangement, as shown in FIG. 9, the concentration difference of the electrolyte 18 becomes large in the height direction of the negative electrode plate 14, but as shown in FIG. 3, by placing the battery horizontally, the concentration difference of the electrolyte 18 in the height direction of the negative electrode plate 14 becomes small, so that the electrolyte 18 can be used evenly for charging and discharging, and as a result, it is thought that the cycle life is significantly improved.
[0014] As described above, the positive electrode plate 12, the hydroxide ion conductive separator 16, and the negative electrode plate 14 are stacked vertically in a "horizontal" state, so that the unit cell is arranged "horizontally". Here, in this specification, "horizontally" means that the main surface of the object (i.e., the plate surface of the electrode plate or the membrane surface of the separator) is approximately parallel to a horizontal plane. However, the terms "horizontally" and "parallel" should not be interpreted strictly, and it is acceptable for the object to have an inclination that can be recognized as horizontal or approximately parallel (to the horizontal plane) in light of common sense or accepted social conventions. Therefore, "horizontally" does not need to be completely parallel, i.e., the angle between the horizontal plane and the main surface is 0 degrees, but the angle between the horizontal plane and the main surface may be less than 30 degrees, less than 20 degrees, less than 10 degrees, or less than 5 degrees.
[0015] According to a preferred embodiment of the present invention, as shown in Fig. 3, the battery may be in the form of a positive / negative electrode laminate, which includes a plurality of positive electrode plates 12, a plurality of negative electrode plates 14, and a plurality of separators 16, and is laminated so that the unit of positive electrode plate 12 / separator 16 / negative electrode plate 14 is repeated. That is, the nickel-zinc secondary battery 10 according to this embodiment has a plurality of unit cells 10a, and the plurality of unit cells 10a are vertically stacked in a horizontal state to form a multi-layer cell as a whole. This is the configuration of a so-called assembled battery or laminated battery, and is advantageous in that a high voltage and a large current can be obtained.
[0016] The positive electrode plate 12 includes a positive electrode active material layer 12a. The positive electrode active material constituting the positive electrode active material layer 12a includes nickel hydroxide and / or nickel oxyhydroxide. Typically, the positive electrode plate 12 further includes a positive electrode current collector (not shown), and the positive electrode current collector preferably has a positive electrode current collector tab 12b extending from an end (e.g., an upper end) of the positive electrode plate 12. A preferred example of the positive electrode current collector is a nickel porous substrate such as a foamed nickel plate. In this case, for example, a paste containing an electrode active material such as nickel hydroxide is uniformly applied to a nickel porous substrate and dried to preferably produce a positive electrode plate consisting of a positive electrode / positive electrode current collector. At that time, it is also preferred to perform a press treatment on the dried positive electrode plate (i.e., the positive electrode / positive electrode current collector) to prevent the electrode active material from falling off and improve the electrode density. The positive electrode plate 12 shown in FIGS. 1, 2, and 4 includes a positive electrode current collector (e.g., foamed nickel), but is not shown. This is because in the case of a nickel-zinc secondary battery, the positive electrode current collector is completely integrated with the positive electrode active material, and therefore the positive electrode current collector cannot be depicted separately. The nickel-zinc secondary battery 10 preferably further includes a positive electrode current collector plate 25 connected to the tip of the positive electrode current collector tab 12b, and more preferably, a plurality of positive electrode current collector tabs 12b are connected to one positive electrode current collector plate 25. This allows current collection to be performed with a simple configuration and with good space efficiency, and also makes it easier to connect to the positive electrode terminal 26. The positive electrode current collector plate 25 itself may be used as the positive electrode terminal 26.
[0017] The positive electrode plate 12 may contain at least one additive selected from the group consisting of silver compounds, manganese compounds, and titanium compounds, which can promote a positive electrode reaction that absorbs hydrogen gas generated by a self-discharge reaction. The positive electrode plate 12 may further contain cobalt. Cobalt is preferably contained in the positive electrode plate 12 in the form of cobalt oxyhydroxide. In the positive electrode plate 12, cobalt functions as a conductive additive, thereby contributing to an improvement in charge / discharge capacity.
[0018] The negative electrode plate 14 includes a negative electrode active material layer. The negative electrode active material constituting the negative electrode active material layer includes at least one selected from the group consisting of zinc, zinc oxide, zinc alloys, and zinc compounds. Zinc may be included in any form of zinc metal, zinc compound, or zinc alloy, so long as it has electrochemical activity suitable for the negative electrode. Preferred examples of the negative electrode material include zinc oxide, zinc metal, calcium zincate, and the like, with a mixture of zinc metal and zinc oxide being more preferred. The negative electrode active material may be configured in a gel form, or may be mixed with an electrolyte to form a negative electrode mixture. For example, a gelled negative electrode can be easily obtained by adding an electrolyte and a thickener to the negative electrode active material. Examples of the thickener include polyvinyl alcohol, polyacrylate, CMC, alginic acid, and the like, with polyacrylic acid being preferred because of its excellent chemical resistance to strong alkalis.
[0019] As the zinc alloy, a zinc alloy containing no mercury or lead, known as a mercury-free zinc alloy, can be used. For example, a zinc alloy containing 0.01 to 0.1 mass% indium, 0.005 to 0.02 mass% bismuth, and 0.0035 to 0.015 mass% aluminum is preferable because it has an effect of suppressing hydrogen gas generation. In particular, indium and bismuth are advantageous in terms of improving discharge performance. The use of a zinc alloy for the negative electrode can improve safety by suppressing hydrogen gas generation by slowing down the self-dissolution rate in an alkaline electrolyte.
[0020] The shape of the negative electrode material is not particularly limited, but it is preferably in powder form, which increases the surface area and allows for high-current discharge. The average particle size of the negative electrode material is preferably in the range of 3 to 100 μm in minor axis in the case of a zinc alloy, and within this range, the large surface area makes it suitable for high-current discharge, and it is easy to mix uniformly with the electrolyte and gelling agent, and is easy to handle when assembling a battery.
[0021] As shown in FIG. 4, the negative electrode plate 14 includes a negative electrode current collector 14b provided inside and / or on the surface of the negative electrode active material layer 14a (except for the portion extending as the negative electrode current collector tab 14c). That is, the negative electrode active material layer 14a may be provided on both sides of the negative electrode current collector 14b, or the negative electrode active material layer 14a may be provided on only one side of the negative electrode current collector 14b. The negative electrode plate 14 further includes a negative electrode current collector 14b, and the negative electrode current collector 14b preferably has a negative electrode current collector tab 14c extending from an end of the negative electrode plate 14. The negative electrode current collector tab 14c is preferably provided at a position that does not overlap with the positive electrode current collector tab 12b. The nickel-zinc secondary battery 10 preferably further includes a negative electrode current collector plate 27 connected to the tip of the negative electrode current collector tab 14c, and more preferably, a plurality of negative electrode current collector tabs 14c are connected to one negative electrode current collector plate 27. This allows current collection to be performed with a simple configuration and with good space efficiency, and also makes it easier to connect to the negative electrode terminal 28. Furthermore, the negative electrode current collecting plate 27 itself may be used as the negative electrode terminal 28.
[0022] The negative electrode current collector 14b is preferably a metal plate having a plurality (or a large number) of openings from the viewpoint of fixing the negative electrode active material to the current collector. Preferred examples of such a negative electrode current collector 14b include expanded metal, punched metal, metal mesh, and combinations thereof, more preferably copper expanded metal, copper punched metal, and combinations thereof, and particularly preferably copper expanded metal. In this case, for example, a mixture containing zinc oxide powder and / or zinc powder, and optionally a binder (e.g., polytetrafluoroethylene particles) can be applied onto the copper expanded metal to preferably prepare a negative electrode plate consisting of a negative electrode / a negative electrode current collector. In this case, it is also preferable to perform a press treatment on the negative electrode plate (i.e., a negative electrode / a negative electrode current collector) after drying to prevent the electrode active material from falling off and improve the electrode density. The expanded metal is a mesh-shaped metal plate obtained by pressing and expanding a metal plate while making staggered cuts using an expander, and shaping the cuts into a diamond or tortoiseshell shape. Punching metal, also known as perforated metal, is a metal plate with holes punched into it. Metal mesh is a metal product with a wire mesh structure, and is different from expanded metal and punching metal.
[0023] The hydroxide ion conductive separator 16 is provided so as to separate the positive electrode plate 12 and the negative electrode plate 14 in a manner allowing hydroxide ion conductivity. For example, as shown in FIG. 4, the negative electrode plate 14 may be configured to be covered or wrapped with the hydroxide ion conductive separator 16. This makes it possible to fabricate a nickel-zinc secondary battery (particularly a laminated battery thereof) capable of preventing zinc dendrite extension extremely easily and with high productivity, without the need for a complicated sealing joint between the hydroxide ion conductive separator 16 and the battery case. However, a simple configuration in which the hydroxide ion conductive separator 16 is disposed on one side of the positive electrode plate 12 or the negative electrode plate 14 may also be used.
[0024] The hydroxide ion conductive separator 16 is not particularly limited as long as it is a separator capable of isolating the positive electrode plate 12 and the negative electrode plate 14 in a hydroxide ion conductive manner, but is typically a separator that includes a hydroxide ion conductive solid electrolyte and selectively passes hydroxide ions solely by utilizing hydroxide ion conductivity. A preferred hydroxide ion conductive solid electrolyte is a layered double hydroxide (LDH) and / or an LDH-like compound. Therefore, the hydroxide ion conductive separator 16 is preferably an LDH separator. In this specification, an "LDH separator" is defined as a separator that includes an LDH and / or an LDH-like compound and selectively passes hydroxide ions solely by utilizing the hydroxide ion conductivity of the LDH and / or the LDH-like compound. In this specification, an "LDH-like compound" is a hydroxide and / or oxide with a layered crystal structure similar to LDH, which may not be called LDH, and can be said to be equivalent to LDH. However, in a broad sense, "LDH" can be interpreted as including not only LDH but also LDH-like compounds. The LDH separator is preferably composited with a porous substrate. Therefore, the LDH separator preferably further comprises a porous substrate, and is composited with the porous substrate in a form in which the pores of the porous substrate are filled with LDH and / or LDH-like compounds. That is, in a preferred LDH separator, the pores of the porous substrate are blocked with LDH and / or LDH-like compounds so as to exhibit hydroxide ion conductivity and gas impermeability (and therefore function as an LDH separator exhibiting hydroxide ion conductivity). The porous substrate is preferably made of a polymer material, and it is particularly preferred that the LDH is incorporated over the entire thickness of the porous substrate made of a polymer material. For example, known LDH separators such as those disclosed in Patent Documents 1 to 7 can be used. The thickness of the LDH separator is preferably 5 to 100 μm, more preferably 5 to 80 μm, even more preferably 5 to 60 μm, and particularly preferably 5 to 40 μm.
[0025] The nickel-zinc secondary battery 10 may further include a liquid-retaining member 17 in contact with the positive electrode plate 12 and / or the negative electrode plate 14. For example, it is preferable that not only the hydroxide ion conductive separator 16 but also the liquid-retaining member 17 is interposed between the positive electrode plate 12 and the negative electrode plate 14. As shown in FIG. 4, it is preferable that the positive electrode plate 12 and / or the negative electrode plate 14 is covered or wrapped with the liquid-retaining member 17. However, a simple configuration in which the liquid-retaining member 17 is disposed on one side of the positive electrode plate 12 or the negative electrode plate 14 may also be used. In any case, by interposing the liquid-retaining member 17, the positive electrode plate 12 and / or the negative electrode plate 14 are preferably covered or wrapped with the liquid-retaining member 17. or The electrolyte can be evenly distributed between the negative electrode plate 14 and the hydroxide ion conductive separator 16, and the positive electrode plate 12 and / or or Hydroxide ions can be efficiently exchanged between the negative electrode plate 14 and the hydroxide ion conductive separator 16. The liquid-retaining member 17 is not particularly limited as long as it is a member capable of retaining an electrolyte, but is preferably a sheet-like member. Preferred examples of the liquid-retaining member 17 include nonwoven fabric, water-absorbent resin, liquid-retaining resin, porous sheet, and various spacers, but nonwoven fabric is particularly preferred because it allows a negative electrode structure with good performance to be produced at low cost. The liquid-retaining member 17 or nonwoven fabric preferably has a thickness of 10 to 200 μm, more preferably 20 to 200 μm, even more preferably 20 to 150 μm, particularly preferably 20 to 100 μm, and most preferably 20 to 60 μm. If the thickness is within the above range, a sufficient amount of electrolyte can be retained in the liquid-retaining member 17 while keeping the overall size of the positive electrode structure and / or negative electrode structure compact and without waste.
[0026] When the positive electrode plate 12 and / or the negative electrode plate 14 are covered or wrapped with the liquid retaining member 17 and / or the separator 16, it is preferable that the outer edge of the positive electrode plate 12 and / or the separator 16 is closed (except for the edge from which the positive electrode current collector tab 12b and the negative electrode current collector tab 14c extend). In this case, it is preferable that the closed edge of the outer edge of the liquid retaining member 17 and / or the separator 16 is realized by folding the liquid retaining member 17 and / or the separator 16, or by sealing the liquid retaining members 17 together and / or the separators 16 together. Examples of the sealing method include adhesives, heat welding, ultrasonic welding, adhesive tape, sealing tape, and combinations thereof. In particular, since the LDH separator including the porous base material made of a polymer material has an advantage that it is flexible and therefore easy to bend, it is preferable to form the LDH separator into a long shape and fold it to form a state in which one side of the outer edge is closed. Thermal welding and ultrasonic welding may be performed using a commercially available heat sealer or the like, but in the case of sealing between LDH separators, it is preferable to perform thermal welding and ultrasonic welding by sandwiching the outer peripheral portion of the liquid retaining member 17 between the LDH separators constituting the outer peripheral portion, in order to perform more effective sealing. On the other hand, the adhesive, adhesive tape, and sealing tape may be commercially available products, but it is preferable to use those containing a resin having alkali resistance in order to prevent deterioration in an alkaline electrolyte. From this viewpoint, examples of preferable adhesives include epoxy resin adhesives, natural resin adhesives, modified olefin resin adhesives, and modified silicone resin adhesives, and among them, epoxy resin adhesives are more preferable because they are particularly excellent in alkali resistance. An example of a product of an epoxy resin adhesive is the epoxy adhesive Hysol (registered trademark) (manufactured by Henkel).
[0027] The electrolyte preferably contains an aqueous solution of an alkali metal hydroxide. Examples of the alkali metal hydroxide include potassium hydroxide, sodium hydroxide, lithium hydroxide, ammonium hydroxide, etc., with potassium hydroxide being more preferred. In order to suppress the self-dissolution of zinc and / or zinc oxide, a zinc compound such as zinc oxide or zinc hydroxide may be added to the electrolyte. As described above, the electrolyte may be mixed with a positive electrode active material and / or a negative electrode active material to be present in the form of a positive electrode mixture and / or a negative electrode mixture. In addition, the electrolyte may be gelled to prevent leakage of the electrolyte. As the gelling agent, it is preferable to use a polymer that absorbs the solvent of the electrolyte and swells, and polymers such as polyethylene oxide, polyvinyl alcohol, polyacrylamide, etc., or starch are used.
[0028] The battery case 20 is preferably made of resin. The resin constituting the battery case 20 is preferably a resin resistant to alkali metal hydroxides such as potassium hydroxide, more preferably a polyolefin resin, ABS resin, or modified polyphenylene ether, and even more preferably an ABS resin or modified polyphenylene ether. The battery case 20 may have a pressure relief valve for releasing gas. In addition, a group of cases in which two or more battery cases 20 are arranged may be housed in an outer frame to form a battery module.
[0029] LDH-like compounds According to a preferred embodiment of the present invention, the LDH separator may contain an LDH-like compound. The definition of the LDH-like compound is as described above. Preferred LDH-like compounds are: (a) a hydroxide and / or oxide having a layered crystal structure containing Mg and one or more elements including at least Ti selected from the group consisting of Ti, Y, and Al, or (b) a hydroxide and / or oxide having a layered crystal structure containing (i) Ti, Y, and optionally Al and / or Mg, and (ii) an additional element M which is at least one selected from the group consisting of In, Bi, Ca, Sr, and Ba; or (c) a hydroxide and / or oxide having a layered crystal structure containing Mg, Ti, Y, and optionally Al and / or In, wherein the LDH-like compound in (c) is In(OH) 3 It exists in the form of a mixture with
[0030] According to a preferred embodiment (a) of the present invention, the LDH-like compound may be a hydroxide and / or oxide having a layered crystal structure containing Mg and one or more elements including at least Ti selected from the group consisting of Ti, Y, and Al. Thus, a typical LDH-like compound is a composite hydroxide and / or composite oxide of Mg, Ti, optionally Y, and optionally Al. The above elements may be replaced with other elements or ions to the extent that the basic properties of the LDH-like compound are not impaired, but it is preferable that the LDH-like compound does not contain Ni. For example, the LDH-like compound may further contain Zn and / or K. This can further improve the ionic conductivity of the LDH separator.
[0031] LDH-like compounds can be identified by X-ray diffraction. Specifically, when X-ray diffraction is performed on the surface of the LDH separator, peaks derived from LDH-like compounds are typically detected in the range of 5°≦2θ≦10°, more typically in the range of 7°≦2θ≦10°. As described above, LDH has exchangeable anions and H as intermediate layers between stacked hydroxide base layers. 2 O is present. In this regard, when LDH is measured by X-ray diffraction, a peak due to the crystal structure of LDH (i.e., the (003) peak of LDH) is essentially detected at 2θ=11-12°. In contrast, when an LDH-like compound is measured by X-ray diffraction, a peak is typically detected in the above-mentioned range shifted to the lower angle side from the above-mentioned peak position of LDH. In addition, the interlayer distance of the layered crystal structure can be determined by the Bragg formula using 2θ corresponding to the peak derived from the LDH-like compound in X-ray diffraction. The interlayer distance of the layered crystal structure constituting the LDH-like compound determined in this way is typically 0.883-1.8 nm, more typically 0.883-1.3 nm.
[0032] In the LDH separator according to the above aspect (a), the atomic ratio of Mg / (Mg+Ti+Y+Al) in the LDH-like compound determined by energy dispersive X-ray analysis (EDS) is preferably 0.03 to 0.25, more preferably 0.05 to 0.2. The atomic ratio of Ti / (Mg+Ti+Y+Al) in the LDH-like compound is preferably 0.40 to 0.97, more preferably 0.47 to 0.94. The atomic ratio of Y / (Mg+Ti+Y+Al) in the LDH-like compound is preferably 0 to 0.45, more preferably 0 to 0.37. The atomic ratio of Al / (Mg+Ti+Y+Al) in the LDH-like compound is preferably 0 to 0.05, more preferably 0 to 0.03. Within the above ranges, the alkali resistance is more excellent, and the effect of suppressing short circuits caused by zinc dendrites (i.e., dendrite resistance) can be more effectively realized. Regarding LDH separators, conventionally known LDHs have the general formula: M 2+ 1-x M 3+ x (OH) 2 A n- x / n mH 2 O (where M 2+ is a divalent cation, M 3+ is a trivalent cation, and A n- is an n-valent anion, n is an integer of 1 or more, x is 0.1 to 0.4, and m is 0 or more). In contrast, the above atomic ratio in the LDH-like compound generally deviates from the above general formula of LDH. For this reason, it can be said that the LDH-like compound in this embodiment generally has a composition ratio (atomic ratio) different from that of conventional LDH. It is preferable to perform the EDS analysis using an EDS analyzer (e.g., X-act, manufactured by Oxford Instruments) by 1) capturing an image at an accelerating voltage of 20 kV and a magnification of 5,000 times, 2) performing three-point analysis with an interval of about 5 μm in the point analysis mode, 3) repeating the above 1) and 2) once more, and 4) calculating the average value of a total of six points.
[0033] According to another preferred embodiment (b) of the present invention, the LDH-like compound may be a hydroxide and / or oxide having a layered crystal structure, comprising (i) Ti, Y, and optionally Al and / or Mg, and (ii) an additional element M. Thus, a typical LDH-like compound is a composite hydroxide and / or composite oxide of Ti, Y, the additional element M, optionally Al, and optionally Mg. The additional element M is In, Bi, Ca, Sr, Ba, or a combination thereof. The above elements may be replaced with other elements or ions to the extent that the basic properties of the LDH-like compound are not impaired, but it is preferred that the LDH-like compound does not contain Ni.
[0034] In the LDH separator according to the above aspect (b), the atomic ratio of Ti / (Mg+Al+Ti+Y+M) in the LDH-like compound determined by energy dispersive X-ray analysis (EDS) is preferably 0.50 to 0.85, more preferably 0.56 to 0.81. The atomic ratio of Y / (Mg+Al+Ti+Y+M) in the LDH-like compound is preferably 0.03 to 0.20, more preferably 0.07 to 0.15. The atomic ratio of M / (Mg+Al+Ti+Y+M) in the LDH-like compound is preferably 0.03 to 0.35, more preferably 0.03 to 0.32. The atomic ratio of Mg / (Mg+Al+Ti+Y+M) in the LDH-like compound is preferably 0 to 0.10, more preferably 0 to 0.02. The atomic ratio of Al / (Mg+Al+Ti+Y+M) in the LDH-like compound is preferably 0 to 0.05, more preferably 0 to 0.04. Within the above range, the alkali resistance is more excellent, and the effect of suppressing short circuits caused by zinc dendrites (i.e., dendrite resistance) can be more effectively realized. Incidentally, LDHs conventionally known as LDH separators are represented by the general formula: M 2+ 1-x M 3+ x (OH) 2 A n- x / n mH 2 O (where M 2+ is a divalent cation, M 3+ is a trivalent cation, and An- is an n-valent anion, n is an integer of 1 or more, x is 0.1 to 0.4, and m is 0 or more). In contrast, the above atomic ratio in the LDH-like compound generally deviates from the above general formula of LDH. For this reason, it can be said that the LDH-like compound in this embodiment generally has a composition ratio (atomic ratio) different from that of conventional LDH. It is preferable to perform the EDS analysis using an EDS analyzer (e.g., X-act, manufactured by Oxford Instruments) by 1) capturing an image at an accelerating voltage of 20 kV and a magnification of 5,000 times, 2) performing three-point analysis with an interval of about 5 μm in the point analysis mode, 3) repeating the above 1) and 2) once more, and 4) calculating the average value of a total of six points.
[0035] According to yet another preferred embodiment (c) of the present invention, the LDH-like compound is a hydroxide and / or oxide of a layered crystal structure containing Mg, Ti, Y, and optionally Al and / or In, and the LDH-like compound is In(OH) 3 The LDH-like compound of this embodiment is a hydroxide and / or oxide having a layered crystal structure containing Mg, Ti, Y, and optionally Al and / or In. Thus, a typical LDH-like compound is a composite hydroxide and / or composite oxide of Mg, Ti, Y, optionally Al, and optionally In. The In that can be contained in the LDH-like compound includes not only In that is intentionally added to the LDH-like compound, but also In(OH) 3 The above elements may be unavoidably mixed into the LDH-like compound due to the formation of Ni. The above elements may be replaced with other elements or ions to the extent that the basic properties of the LDH-like compound are not impaired, but it is preferable that the LDH-like compound does not contain Ni. Incidentally, the LDH conventionally known for the LDH separator has the general formula: M 2+ 1-x M 3+ x (OH) 2 A n- x / n mH 2 O (where M 2+ is a divalent cation, M 3+ is a trivalent cation, and An- is an n-valent anion, n is an integer of 1 or more, x is 0.1 to 0.4, and m is 0 or more). In contrast, the atomic ratio in the LDH-like compound generally deviates from the above general formula of LDH. Therefore, it can be said that the LDH-like compound in this embodiment generally has a composition ratio (atomic ratio) different from that of conventional LDH.
[0036] The mixture according to embodiment (c) contains not only LDH-like compounds but also In(OH) 3 (typically LDH-like compounds and In(OH) 3 It consists of In(OH) 3 The inclusion of In(OH) in the mixture can effectively improve the alkali resistance and dendrite resistance of the LDH separator. 3 The content of In(OH) is preferably an amount that can improve the alkali resistance and dendrite resistance of the LDH separator without substantially impairing the hydroxide ion conductivity, and is not particularly limited. 3 may have a cubic crystal structure, In(OH) 3 The crystal may be surrounded by an LDH-like compound. 3 can be identified by X-ray diffraction. EXAMPLES
[0037] The present invention will now be further illustrated by the following examples.
[0038] Example 1 (1) Preparation of nickel-zinc secondary battery The following positive electrode plate, negative electrode plate, LDH separator, nonwoven fabric, battery case, and electrolyte were prepared. Positive electrode plate: A 0.7 mm thick plate made by filling the pores of nickel foam with positive electrode paste containing nickel hydroxide and a binder and then drying (an uncoated area near one end of the nickel foam where no positive electrode paste is applied is pressed to form a positive electrode current collecting tab). Negative electrode plate: A negative electrode paste containing 92.7 vol% ZnO powder, 2.9 vol% metallic Zn powder, 3.1 vol% polytetrafluoroethylene (PTFE), and propylene glycol is pressed onto a current collector (copper expanded metal) (there is an uncoated area near one end of the copper expanded metal where the negative electrode paste is not applied, which serves as a negative electrode current collecting tab). LDH separator: Ni-Al-Ti-LDH (layered double hydroxide) is deposited on the inside and surface of a polyethylene microporous membrane by hydrothermal synthesis and then roll-pressed. Thickness: 9μm Non-woven fabric: Polypropylene, thickness 100μm Battery case: Modified polyphenylene ether resin housing Electrolyte: 5.4mol / L KOH solution with 0.4mol / L ZnO dissolved in it
[0039] The positive electrode plate was wrapped in nonwoven fabric so as to cover both sides, so that the nonwoven fabric slightly protruded from the remaining three sides except for the side from which the positive electrode current collector tab extended. The excess portion of the nonwoven fabric protruding from the three sides of the positive electrode plate was heat-sealed with a heat seal bar to obtain a positive electrode structure. The negative electrode plate was also wrapped in nonwoven fabric and LDH separator in order from both sides, so that the nonwoven fabric and LDH separator slightly protruded from the remaining three sides except for the side from which the negative electrode current collector tab extended. The excess portion of the nonwoven fabric and LDH separator protruding from the three sides of the negative electrode plate was heat-sealed with a heat seal bar to obtain a negative electrode structure. In this way, a total of three electrode structures consisting of two positive electrode structures and one negative electrode structure were prepared. The negative electrode structure was sandwiched between two positive electrode structures and placed in a battery case. The positive electrode current collector was connected to the positive electrode current collector terminal, and the negative electrode current collector was connected to the negative electrode current collector terminal, and the resin case and the resin lid were integrated by thermal welding. Then, an electrolyte was added from the electrolyte injection port, and the electrolyte was sufficiently permeated into the positive and negative electrode plates by evacuation or the like. Then, the electrolyte injection port was closed to form a sealed cell.
[0040] (2) Cycle testing Using a charge / discharge device (TOSCAT3000S, manufactured by Toyo Systems Co., Ltd.), the sealed cell was subjected to formation by charging at 0.1 C and discharging at 0.2 C. Then, a charge / discharge cycle was performed at 1 C. The charge / discharge cycle was repeated under the same conditions, and the number of charge / discharge cycles until the discharge capacity of the sealed cell decreased to 70% of the discharge capacity of the first cycle was recorded.
[0041] Example 2 (comparison) As shown in FIGS. 6 and 7, the cycle test was carried out in the same manner as in Example 1, except that the battery was placed at an angle of 45 degrees to the horizontal.
[0042] Example 3 (comparison) The cycle test was carried out in the same manner as in Example 1, except that the battery was placed vertically at 90 degrees to the horizontal plane, as shown in FIGS.
[0043] result The results of Examples 1 to 3 are shown in Table 1. From the results shown in Table 1, it can be seen that the cycle life was significantly improved by placing the battery horizontally.
[0044] [Table 1] [Explanation of symbols]
[0045] 10 Nickel-zinc secondary battery 10a Unit cell 11 Battery elements 12 Positive plate 12a Cathode active material layer 12b Positive electrode current collecting tab 14 Negative plate 14a Negative electrode active material layer 14b Negative electrode current collector 14c Negative electrode current collecting tab 16 Hydroxide ion conducting separator 17 Liquid retaining material 18 Electrolyte 20 Battery case 25 Positive electrode current collector 26 Positive terminal 27 Negative electrode current collector 28 Negative terminal
Claims
1. a positive electrode plate including a positive electrode active material layer including nickel hydroxide and / or nickel oxyhydroxide; a negative electrode plate including a negative electrode active material layer including at least one selected from the group consisting of zinc, zinc oxide, a zinc alloy, and a zinc compound; a hydroxide ion conductive separator that separates the positive electrode plate and the negative electrode plate so as to be capable of conducting hydroxide ions; an electrolyte in which the positive electrode plate, the negative electrode plate, and the hydroxide ion conductive separator are immersed; wherein the positive electrode plate, the hydroxide ion conducting separator and the negative electrode plate are stacked vertically in a horizontal orientation, thereby arranging the unit cells horizontally; A stationary nickel-zinc secondary battery, in which not only the hydroxide ion conductive separator but also a liquid-retaining material is interposed between the positive electrode plate and the negative electrode plate, and the positive electrode plate and / or the negative electrode plate are enclosed by the liquid-retaining material.
2. 2. The stationary nickel-zinc secondary battery according to claim 1, wherein the liquid retaining member is a nonwoven fabric.
3. 3. The stationary nickel-zinc secondary battery of claim 1 or 2, wherein the hydroxide ion conducting separator is a layered double hydroxide (LDH) separator comprising an LDH and / or an LDH-like compound.
4. 4. The stationary nickel-zinc secondary battery according to claim 3, wherein the LDH separator further comprises a porous substrate, and the LDH and / or LDH-like compound is composited with the porous substrate in a form filled in the pores of the porous substrate.
5. 5. The stationary nickel-zinc secondary battery of claim 4, wherein the porous substrate is made of a polymeric material.
6. The stationary nickel-zinc secondary battery according to any one of claims 1 to 5, comprising a plurality of the unit cells, the plurality of unit cells being vertically stacked in a horizontal orientation to form a multi-layer cell as a whole.
Citation Information
Patent Citations
Nickel zinc battery
JP2016129156A
Zinc secondary cell
WO2013118561A1
Method for forming layered double hydroxide dense membrane
WO2016067884A1
Separator structure body for use in zinc secondary battery
WO2016076047A1
Battery and assembly method therefor
WO2016147497A1